EXAMINING THE FACTORS AFFECTING THE FUNDING SUCCESS OF CROWDFUNDING PROJECTS WITH THE ANALYTICAL NETWORK PROCESS: THE CASE OF TURKIYE (Third Sector Social Economic Review, 2025)
Crowdfunding is the financing of a project or venture by groups and individuals using online methods, through relatively small contributions instead of traditional funding sources. Crowdfunding practices, which began around 2000, continue to spread both globally and in Turkiye. The aim of this study, conducted within the context of the concept, is to identify the factors that influence the success of crowdfunding projects during the funding process and to determine the priority level of each of these factors. In this study, which examines projects on crowdfunding platforms operating in Turkiye, the factors contributing to success during the funding process were analyzed using the Analytical Network Process method. In this context, the factors identified as influencing funding success were grouped under seven categories: market and target audience, product and production, team, business plan, financial statements, images/videos, and management. Among these factors, ""market and target audience,"" ""product and production,"" and ""team"" were determined to be the highest-priority success factors, while ""management,"" ""images/videos,"" and ""financial statements"" were identified as the lowest-priority success factors. The results are expected to guide entrepreneurs and contribute to the more effective management of crowdfunding projects.
Keywords: Analytic Network Process; Crowdfunding; Entrepreneurship; Financing; Success Factors